The Effect of Product Knowledge, Perceived Benefit and Hospital Brand Image on Patient Decisions to Undergo Eracs (Case Study on ERACS Patients at RSIA Puri Betik Hati) - Hastuti , Nike Septembriana Lestari (Yayasan Gema Bina Nusantara, 2025)
ERACS or Enhanced Recovery After Caesarean Surgery is a caesarean section delivery with a special method to help speed up the recovery process. ERACS is a service for mothers who want to give birth that has many benefits, both during labor and postpartum. But unfortunately, there are still many patients who do not know well about the benefits of ERACS or about ERACS itself. This problem is also faced by Puri Betik Hospital. Therefore, this study was conducted to find out how product knowledge, perceived benefits and hospital brand image can influence patient decisions to undergo ERACS at RSIA Puri Betik. This research is included in the type of quantitative research, with the number of samples set at 249 respondents, the data collection technique used is a questionnaire and the data analysis technique used is PLS-SEM. The results showed that all independent variables in this study, namely product knowledge, perceived benefits and hospital brand image, significantly influenced ERACS patient decisions at RSIA Puri Betik.